Hybrid Contract Dalam Perspektif Maqhosid Al-Syari’ah Jasser Auda - Ahmad Insya Ansori; Moh. Ulumuddin (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2021)
Background. The development of the Islamic finance industry and the demands of modern financial transactions encourage innovation in contracts to respond to the increasingly complex needs of society. Aim. This study aims to determine the relevance of the Hybrid Contract concept with Maqashid al-Shari’ah introduced by Jasser Auda, as well as to explain how the law applies to Hybrid Contracts in the modern financial industry. Methods. The research uses a qualitative approach, which includes three stages, namely description, formulation and interpretation. Results. Hybrid Contract is a collection of several contracts contained in a contract that is agreed upon by both parties, both jointly and reciprocally, so that all legal consequences of the collected contracts and all rights and obligations arising from it are seen as a single entity that cannot be changed and separated. DSN-MUI in an effort to combine contracts took two models, namely multiple contracts (mujtami’ah) and multiple contracts (muta’addidah). Faced with Maqashid al-Shari’ah Jasser Auda, Hybrid Contracts are relevant in an effort to validate all cognition, holism, multi-dimensionality and intent.